JAZZ SOM TRANSNATIONAL POPULÆRKULTUR FRA EN LOKAL BIOTOPS PERSPEKTIV - Knudsen, Knud; Mortensen, Tore (Temp - tidsskrift for historie, 2013)
ABSTRACT Jazz as Transnational Popular Culture: The Perspective of a Local Biotope In the article, we explore the “diaspora of jazz”. The empirical foundation is our study of the development of jazz in the provincial town of Aalborg. The article takes its theoretical inspiration from Bruce Johnson’s critique of traditional historiography of jazz, portraying it solely as a history of the musical development of jazz. The argument is that jazz should not only be seen as a musical practice but also as a social and a cultural practice. Jazz was played in Aalborg from the early 1920s but didn’t receive its popular breakthrough until the mid-1950s. The general argument is that jazz in the 1950s represented a distinct musical practice – autodidact musicians learning the new music by listening to records, “do-it-yourself” in the words of Eric Hobsbawm, but that the social practice (jazz dancing) and the cultural practice (the self-organized club milieu) were just as important aspects of the break-through of jazz as popular music and culture. The traditional jazz (dixieland) remains to this day the favorite musical culture of the generation of the 1950s, when new generations in the 1960s and later turned to rock’n’roll, beat, folk or fusion music styles. Finally, we look at the channels of musical dissemination, being more “irregular” and intertwined than what is generally depicted in jazz literature.